Lived experiences of migrant female youth : the case of refugees in a selected church in Musina, South Africa - Mamadi, Khutso (My University, 2021)
This study presents qualitative findings on lived experiences of migrant female youth in Musina, Limpopo Province, South Africa. Studies reveal that young females, more especially those from the African continent, migrate to foreign countries in large numbers for better livelihoods. A growing number of women, African women in particular, migrate more than ever to meet their own or their families’ economic needs. Some, of course, flee from wars and mostly migrate for better living conditions. Several studies show that many of these women migrate to South Africa. This is because South Africa is amongst the continent’s most popular destinations for Africa’s female migrants. Upon their arrival in South Africa, studies reveal that migrant female youth are faced with a vast number of challenges such as poverty and exclusion from accessing basic services. It is from this background that this study sought to explore lived experiences of migrant female youth in Musina. Nine female migrant youth accommodated by a church shelter in Musina were purposively and conveniently selected to participate in the study. Semi-structured face to face interviews were used to purposefully collect data that saturated at participant number 9. Thematic data analysis was used with the assistance of the Nvivo software to manage and organise data. The narrative theory was used in the study as it allowed the researcher insight and understanding when migrant female youth narrated their experiences and challenges they encounter as migrants in a foreign country. Findings reveal that many female migrant youths illegally migrate to South Africa in search of better livelihoods that are unavailable in their countries of origin. Furthermore, findings indicated that migrant female youth find themselves living in extreme poverty in the host country. However, the female youth employ various coping strategies for their sustainable livelihoods. They also experience exclusion from accessing healthcare services and face blatant xenophobia in the hands of local South Africans. It can therefore be concluded that migrant female youth face a number of challenges in their everyday lives as migrants in South Africa. It could also be helpful to integrate South Africa’s basic service delivery to include services for female migrant youth.
Thesis ( M.A.( Social Work)) -- University of Limpopo, 2021
Keywords: Female migrants; Female youth; Emmigration and immigration; South Africa -- Emmigration and immigration; Youth -- South Africa -- Social conditions; Women -- Social conditions; Females